Three-step optimization based on a multi-model of rural tourism sites - Qi Li; Mengting Ai; Jing Luo; Yaru Sun; Lingling Tian (PLoS ONE, 2025)
Rural tourism is a vital facet of rural revitalization and balanced urban-rural development efforts. As socio-economic development and policy systems change, the tourism demand market progressively transitions from urban to rural areas. This study, based on ‘quantity-location-capacity’ principles, integrates actual environmental conditions and employs location-allocation and algorithmic models to enhance the accessibility of rural tourism sites in the metropolitan fringe area of Wuhan. The results show: ① Wuhan’s distribution of rural tourism destinations is uneven, with the suburbs demonstrating significantly higher composite accessibility compared to the central urban area; ② Based on this experiment’s results and the costs of optimization, there are eight new potential tourist locations; ③ The disparity in accessibility to Wuhan’s tourist destinations has been reduced, resulting in enhanced tourism efficiency and equity. This study can offer recommendations for rural tourism planning and development strategies and provide references for academic research methods.